Predominance of Non-carbapenemase Producing Carbapenem-Resistant Enterobacterales in South Texas - Black, Cody A.; So, Wonhee; Dallas, Steven S.; Gawrys, Gerard; Benavides, Raymond; Aguilar, Samantha; Chen, Chang-Jui; Shurko, James F.; Lee, Grace C. (Frontiers in Microbiology, 2021)
Background: Carbapenem-resistant Enterobacterales (CRE) pose a significant global public health threat. Resistance among CRE is particularly complex, owing to numerous possible resistance mechanisms and broad definitions. We aimed to characterize the clinical and molecular profiles of CRE in the South Texas region. Materials/methods: We compare clinical, genotypic, and phenotypic profiles among Enterobacterales that are carbapenemase producers (CPE) compared to those that are non-carbapenemase producers (NCPE) in South Texas, USA between 2011 and 2019. Molecular characteristics and resistance mechanisms were analyzed using whole-genome sequences. Results: The majority (59%) of the CRE isolates were NCPE while 41% of isolates harbored carbapenemases, predmonantly blaKPC-type. The most common CPE was K. pneumoniae while majority of Enterobacter cloacae and E. coli were NCPE Among K. pneumoniae, the clonal group 307 has emerged as a predmoninant group and was associated with as many CRE infections as the previous common clonal group 258. Patients with NCPE compared to CPE infections were associated with higher antimicrobial exposure prior to culture collection (days of therapy, 795 vs. 242; p<0.001) and emergency department visits within past 90 days (22% vs. 4%; p=0.011). The all cause 30-day mortality was 21%. Conclusions: This study highlights the diversity of resistance mechanisms underlying CRE in South Texas, with 59% not harboring a carbapenemase. Individuals with NCPE infections were more likely to have had prior antimicrobial therapy and emergency department visits compared to those with CPE. Identification and distinction of these mechanisms by rapid identification of species and carbapenemase would allow for optimal treatment and infection control efforts.